Is the Vertical Transmission of Neotyphodium lolii in Perennial Ryegrass the Only Possible Way to the Spread of Endophytes? - Wiewióra, Barbara (PLoS One, 2015)
Endophytic fungi live their whole life within host tissues usually without any visible symptoms. Their vertical transmission (seed-plant-seed) has been well described and documented. However, horizontal transmission (plant-plant) needs more clarification. The aim of this study was to assess the extent to which endophytes move vertically in ecotypes of perennial ryegrass and whether there is evidence for the horizontal transmission of endophytes. Ecotypes from grasslands in Poland were collected in the form of living plants and used for vertical transmission analysis. Plants, the seed collected from these plants and plants grown from this collected seed were tested for endophytic infection. Provided that all produced seeds were viable and able to germinate and produce seedlings, the vertical transmission of Neotyphodium endophytes in perennial ryegrass ecotypes was nearly complete. For the horizontal transmission experiment, endophyte-hosting plants (E+) and endophyte-free plants (E-) of four cultivars were planted in the field in close proximity on small plots that were frequently mown. These studies revealed that after 7 months of growth next to E+ plants, the characteristic Neotyphodium spp. mycelia were found in E- plants, which was especially true for plants growing in close proximity to the infected plants. The occurrence of horizontal transmission of endophytes has not been previously demonstrated.